2020
DOI: 10.1109/access.2020.3033852
|View full text |Cite
|
Sign up to set email alerts
|

Improving Passive Ankle Foot Orthosis System Using Estimated Ankle Velocity Reference

Abstract: This study aims to investigate an appropriate ankle velocity reference (ωref), which is the average ankle velocity of a certain healthy subject when walking with a certain walking speed. The goal is to improve a Passive Controllable Ankle Foot Orthosis (PICAFO) by implementing the ankle velocity reference. Firstly, the function to estimate ωref, based on walking speed and body mass index (BMI), is obtained from 16 able-bodied subjects walking gait data. The effect of controlled stiffness (based on ωref) to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Because of that, the open-loop FOC driver shown in this study can be further utilized in developing a physiotherapy robot, such as the previous ankle robot by the authors [14]. However, it is important to note that the required torque for ankle application is at least 1 Nm [18]. The assumption is the robot should be able to lift the foot, which is 1.45% of the body weight [34].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Because of that, the open-loop FOC driver shown in this study can be further utilized in developing a physiotherapy robot, such as the previous ankle robot by the authors [14]. However, it is important to note that the required torque for ankle application is at least 1 Nm [18]. The assumption is the robot should be able to lift the foot, which is 1.45% of the body weight [34].…”
Section: Resultsmentioning
confidence: 98%
“…Sensors are used to monitor the patient's ankle movements, joint angles, and forces exerted during therapy. This information is crucial for the control system to adjust the robot's movements and provide appropriate assistance or resistance during the exercises [18], [19]. Common sensors used in ankle rehabilitation robots include encoders, force sensors, and accelerometers [12], [20].…”
Section: Introductionmentioning
confidence: 99%
“…The flexion speed or the ankle velocity of each person might be different. A previous study has shown that ankle velocity is related to the body mass index and walking speed [ 22 , 42 ]. Improvement on the control algorithm should consider this ankle velocity reference in each gait phase because it cannot always be constant.…”
Section: Discussionmentioning
confidence: 99%
“…The supporting scheme or strategy is varied. The flexible AFO [ 16 , 17 , 18 ] and passive controlled AFO [ 19 , 20 , 21 , 22 ] keep the ankle position at a certain angle to avoid the foot drop [ 23 ] or to avoid muscle pain [ 5 , 24 ]. The powered AFO generates ankle movements to force the user to walk normally in several scenarios, such as flat walking [ 25 ], sit-to-standing motions [ 26 ], and ascending and descending stairs [ 27 ].…”
Section: Introductionmentioning
confidence: 99%